Assessment of unintended effects of ditches on ecosystem services provided by Iztaccihuatl-Popocatépetl National Park, Mexico - Núñez, Juan Manuel; Cotler, Helena; Lara Pulido, José Alberto; Cram, Silke; Guevara, Alejandro; Ramírez Santiago, Andrea; Galván Díaz, Eunice (Acta Universitaria, 2022)
The Iztaccíhuatl-Popocatépetl National Park is a remnant of high-mountain conifer forests and grasslands that provides ecosystem services to Mexico City. This research assesses the impact of constructing ditches, through modeling infiltration, soil erosion, and carbon sequestration with the hydrological model SWAT, based on soil information (bulk density, soil organic carbon, and soil depth) obtained from the ditches. The resulting estimates revealed that the construction of ditches negatively impacted the provision of the following ecosystem services: (i) alterations of natural conditions that allow water infiltration in more than 25% of 1 ha in grasslands, and up to 20% of 1 ha in forests; (ii) increase in potential soil erosion by 60%; and (iii) up to 30 217 t and 4522 t of soil organic carbon becoming exposed and prone to mineralization in grasslands and forests, respectively.